The search for best fertilizer combination to increase wheat (Triticum aestivum L.) yield in north-western Ethiopia - Biratu, Gizachew Kebede; Elias, Eyasu; Worku, Abebe; Selassie, Yihenew G.; Gameda, Samuel; Sida, Tesfaye Shiferaw (Elsevier B.V., 2025)
Wheat is among the major cereals of wider importance in the mid-altitudes and highlands of Ethiopia. But wheat yield is quite lower than what could be achievable. To address this gap, Ethiopia introduced the use of blended fertilizer in 2015. However, the response of wheat to these new fertilizers is not known. In this study, we evaluated changes in wheat yield resulting from the application of blended fertilizers relative to common practice. The study also aimed at identifying the rate of blended fertilizer appropriate for wheat production and to evaluate how the inclusion of potassium (K), boron (B), and zinc (Zn) to the blend affects wheat yield. For this study, two groups of treatments were set using RCBD design in two locations over two seasons. While the first group composed of no fertilizer application and five levels of NPSZnB blended fertilizer, the second group contains an additional three different fertilizer rates; including modest rate of NPS compound fertilizer alone and NPS blended with K, B, and Zn. A 100 kg/ha urea was uniformly applied to all treatments, except for the control plots. The findings showed that the new blended fertilizer resulted in significantly lower wheat grain yield compared to the common practice. A closer look at the treatments containing the blended fertilizers showed that the highest wheat grain yield was produced with the application of 300 kg/ha NPSZnB at both Burie (3460 kg/ha) and Farta (2290 kg/ha) sites. Compared with the NPS compound fertilizer at a rate of 100 kg/ha, there was no significant wheat yield advantage following the inclusion of Zn and B in the blend fertilizer. However, the inclusion of K resulted in a substantial increase of wheat grain yield at Farta site, while it significantly reduced yield at Burie site. Though wheat responded to blend fertilizer, the move from application of DAP and urea to the blended fertilizers does not result in significant yield increase as it was intended. Regardless of the quality of grain produced by the application of micronutrients, the inclusion of Zn and B to the blends did not increase wheat grain yield either. However, site-specific application of K is required as wheat significantly responded to K at Farta, but the application negatively affected yield at Burie site.